OncotRF: an online resource for exploration of tRNA-derived fragments in human cancers. Issue 8 (2nd August 2020) - Yao, Dongxia; Sun, Xiwei; Zhou, Liyuan; Amanullah, Md; Pan, Xiaoqing; Liu, Yong; Liang, Mingyu; Liu, Pengyuan; Lu, Yan
ABSTRACT: Transfer RNA-derived fragments (tRFs) are a new class of small non-coding RNAs whose biological roles in cancers are not well understood. Emerging evidence suggests that tRFs are involved in gene regulation at multiple levels. In this study, we constructed an integrative database, OncotRF (http://bioinformatics.zju.edu.cn/OncotRF ), for in silico exploration of tRF functions, and identification of diagnostic and prognostic biomarkers in cancers. The database contains an analysis pipeline for tRF identification and characterization, analysis results of 11, 211 small RNA sequencing samples and 8, 776 RNA sequencing samples, and clinicopathologic annotation data from The Cancer Genome Atlas (TCGA). The results include: tRF identification and quantification across 33 cancers, abnormally expressed tRFs and genes, tRF-gene correlations, tRF-gene networks, survival analyses, and tRF-related functional enrichment analyses. Users are also able to identify differentially expressed tRFs, predict their functions, and assess the relevance of the tRF expression levels to the clinical outcome according to user-defined groups. Additionally, an online Kaplan-Meier plotter is available in OncotRF for plotting survival curves according to user-defined groups. OncotRF will be a valuable online database and functional annotation tool for researchers studying the roles, functions, and mechanisms of tRFs in human cancers.